THE LACK OF HUMAN RESOURCES AT ISLAMIC FINANCIAL INTITUTIONS IN INDONESIA: Case Study Sharia Bank in Indonesia - Juliansyah Noor (LPPM STAI La Tansa Mashiro, 2013)
The research study carried to examine the phenomenon of Islamic Banking Industry in Indonesia.This research is qualitative research and literature study category. The researcher used literature from the books, journals, and reports results of previous researchers. The existence of Islamic sharia human resources development has the world and the hereafter dimensions. Human resources readiness to filled in Islamic banking both quantitative and qualitative. It supported by infrastructure of Islamic economics education. An effective recruitment system has been understood of Islamic philosophy and culture.